Development of a Powder Material Deposition Unit and Process Parameters Identification for Selective Vacuum Manufacturing Rapid Prototyping - Khodprom, Sitichai; Songkrod , Nattawat; Phattanaphibul, Thittikorn (Agriculture and Natural Resources, 2015)
Selective vacuum manufacturing (SVM) is an inexpensive, rapid prototyping technique that applies sand casting and powder sintering processes to fabricate a prototype layer by layer. Poly-lactic acid (PLA) powder, a biodegradable polymer, was considered for part material of SVM, in particular for tissue scaffold fabrication. Previous studies illustrated a problem with incomplete PLA powder deposited in the created cavity due to clogging at the nozzle’s tip. The objective of this paper was to develop a new powder material deposition unit for SVM. A pneumatic cylinder was adopted to provide vertical vibration that can prevent the clogging problem more effectively. The nozzle size and the air pressure used for its operation were varied to identify the suitable process parameters. The results illustrated that using a nozzle size of 18G (internal diameter 0.90 mm) and air pressure of 0.5 bar could provide an average flow rate of 4.312 ± 0.555 mg.s-1 without flow problems.